Intracellular RNA recognition pathway activates strong anti‐viral response in human mast cells. (11th March 2013) - Lappalainen, J.; Rintahaka, J.; Kovanen, P. T.; Matikainen, S.; Eklund, K. K.
Summary Mast cells have been implicated in the first line of defence against parasites and bacteria, but less is known about their role in anti‐viral responses. Allergic diseases often exacerbate during viral infection, suggesting an increased activation of mast cells in the process. In this study we investigated human mast cell response to double‐stranded RNA and viral infection. Cultured human mast cells were incubated with poly(I:C), a synthetic RNA analogue and live Sendai virus as a model of RNA parainfluenza virus infection, and analysed for their anti‐viral response. Mast cells responded to intracellular poly(I:C) by inducing type 1 and type 3 interferons and TNF‐α. In contrast, extracellular Toll‐like receptor 3 (TLR)‐3‐activating poly(I:C) failed to induce such response. Infection of mast cells with live Sendai virus induced an anti‐viral response similar to that of intracellular poly(I:C). Type 1, but not type 3 interferons, up‐regulated the expression of melanoma differentiation–associated gene 5 (MDA‐5) and retinoic acid‐inducible gene‐1 (RIG‐1), and TLR‐3, demonstrating that human mast cells do not express functional receptors for type 3 interferons. Furthermore, virus infection induced the anti‐viral proteins MxA and IFIT3 in human mast cells. In conclusion, our results support the notion that mast cells can recognize an invading virus through intracellular virus sensors and produce high amounts of type 1 and type 3 interferons and the anti‐viral proteins human myxovirus resistance gene A (MxA) and interferon‐induced protein with tetratricopeptide repeats 3 (IFIT3) in response to the virus infection.